Ensino de eletrodinâmica por uma unidade didática baseada nas teorias histórico-cultural e desenvolvimental - Oliveira, Wilson Campos (2019)
A didactic unit was elaborated as a proposal for teaching concepts related to Electrodynamics, thus starting the studies of Physics. The approach of the theme made by this teaching unit is based on the concepts of electric current, potential difference, resistors and Ohm laws, making use and debating the various teaching strategies, such as texts of scientific dissemination, experimentation, teamwork and etc. Seeking to answer the question: How can the implementation of a didactic unit, with different methodological approaches, such as team work, reading of scientific texts and investigative experiments, contribute to the debate and learning of content concepts related to Electrodynamics? As a theoretical framework, Davydov's theory of developmental teaching and Vigotsky's theory of cultural historical learning were used for all activities. The way it was decided to deal with the problem was to provide circumstances that are far beyond the mere act of memorizing the content charged in university entrance exams, turning students into active subjects, or rather protagonists before the activities proposed to them. Activities were carried out whose performance evidenced the research procedures and the way science is developed, contextualized socio-economically and culturally, so that it was possible for students to appropriate the procedures they used to create the numerous physical theories, in order to understand the same way as science is done. The activities were developed in a total of eight fifty-minute classes, with students from the second grade of high school. In order to make it possible for teachers to understand how each activity was done by students, an analysis of all material produced based on Bardin's Content Analysis method (1977) was performed. Directions are pointed through these analyzes, so that teachers who make use of this material have the possibility to improve their activities. Therefore, the educational product will be made available to teachers who show interest in knowing or making use of this material.